Endoscopic ultrasound measurements for detection of residual disease after neoadjuvant chemoradiotherapy for esophageal cancer - van der Bogt, Ruben D.; Noordman, Bo J.; Krishnadath, Kausilia K.; Roumans, Carlijn A. M.; Schoon, Erik J.; Oostenbrug, Liekele E.; Siersema, Peter D.; Vleggaar, Frank P.; van Lanschot, J. Jan B.; Spaander, Manon C. W. (Endoscopy, 2019)
Background Endoscopic ultrasound (EUS) measurements of residual thickness and residual area have been suggested to correlate with histopathological residual tumor after neoadjuvant chemoradiotherapy (nCRT) for esophageal cancer. This study assessed the predictive value of EUS-based measurements using tumor thickness and tumor area before nCRT, and residual thickness and residual area 6 and 12 weeks after completion of nCRT for detection of residual disease. Methods This was a substudy of the diagnostic multicenter preSANO trial. The primary end point of the current study was the percentage of tumor regression grade (TRG) 3 – 4 (> 10 % vital tumor cells) residual disease that was detected using EUS-based measurements. Associations of absolute measurements of residual thickness/area and proportional change compared with baseline were evaluated. In the case of a statistically significant association, optimal cut-offs to distinguish TRG3 – 4 residual disease from TRG1 (no vital tumor cells) were determined using Youden’s J index.Results 138 patients were included. Residual thickness and residual area were statistically significantly associated with TRG3 – 4 residual disease 12 weeks after completion of nCRT (odds ratio 1.36, P < 0.01 and 1.64, P = 0.02, respectively). The cut-off for residual thickness was 4.5 mm, which correctly detected 87 % of TRG3 – 4 residual disease and 52 % of TRG1. The cut-off for residual area was 0.92 cm2, which detected 89 % of TRG3 – 4 residual disease and 40 % of TRG1. Conclusions EUS measurements of residual thickness and residual area adequately detected TRG3 – 4 residual disease with a sensitivity of almost 90 % 12 weeks after completion of nCRT. Hence, residual thickness and residual area may aid in the restaging of esophageal cancer after nCRT.